How do you multiply #-3(2x + 5) • (x² - 3x + 2)#?

1 Answer
May 16, 2017

Answer:

#= -6x^3+3x^2+33x-30#

Explanation:

You are multiplying #3# factors together.

Multiplication is commutative and the associative law also applies here, so you can really multiply them in any order that you like.

I have chosen to multiply the two brackets together first and then multiply that product by #-3# at the end.

#-3xx(2x+5)xx(x^2-3x+2)#

#=-3xx[color(blue)((2x+5)xx(x^2-3x+2))]#

#=-3 xx[color(blue)(2x^3-6x^2+4x+5x^2-15x+10)]" "larr# simplify

#=-3(2x^3-x^2-11x+10)#

#= -6x^3+3x^2+33x-30#